Effect of Exfoliation Corrosion on the Mechanical Properties of Friction Stir Spot Welded 2024-T3 AA Joints - Ramadhan H. Gardi; Abdulkader kadauw; Bertrand Hanschel (Advances in Materials Science and Engineering)
This study aims to detect the impact of preexfoliation corrosion on the efficiency of 2 mm thick 2024-T3 aluminum alloy friction stir spot welded (FSSW) joints. Five specimens of FSSW joints, welded with 620 r·min−1 rotational speed and a dwell time of 10 seconds, were immersed in an exfoliation corrosion solution for five different times: 10 h, 20 h, 30 h, 40 h, and 50 h. The tensile shear load for the noncorroded joint was 3.5 kN. The results showed that the degradation of mechanical properties increased with increasing exposure time, and the joint efficiency drop reached 62% for specimens exposed for 50 h to the corroded solution. As welded FSSW 2024-T3 AA joints exhibited a nugget debonding failure mode and a mixed-mode tensile-shear fracture, in the corroded specimens, only a shear fracture could be seen. The results were attributed to a reduction in the bonding area between the upper and lower sheets due to corrosion.